New materials and surface finishing methods for cold forging tools. (15th February 2010) - Engel, U.; Arbak, M.; Wagner, K.; Volkl, R.
Regarding the ever increasing demand for net shaping, research on innovative technologies on tool material and design becomes an important factor for the overall efficiency and competitiveness. The tools in cold forging have to withstand damaging mechanisms of both fatigue and wear, which may act concurrently at different locations on the tool surface. Therefore, process specific tool material selection and local surface treatment of the tools already at the design stage becomes crucial. In this respect, industrial ceramics, offering a better solution against conventional tool steels in terms of wear resistance, occupies the first part of the research presented in this paper. A ceramic adapted tool design with the consideration of thermal effects has been given. Whereas, the second part of the research deals with the locally optimised surfaces of steel tools in terms of fatigue and wear resistance. Three different surface treatment methods are applied on cold forging tools and the results on tool life have been given.